Creation of Casual Fashion Design with the Source Idea of Jaranan Buto - Damayanti, Ailsa; Arifiana, Deny; Kharnolis, Mein; Nahari, Inty (PT. Riset Press International, 2024)
Jaranan Jaranan Buto folk dance originates from Banyuwangi and refers to the story of Palawan Minakjinggo in the battle against Kebo Mawet. This art is created from the mixture of osing culture with mataraman kingdom. Casual fashion is clothing that is simple, practical, comfortable to wear, and has a loose size and is used in everyday life. Jaranan Buto's clothing has a similar shape to casual clothing. To further introduce the culture of the Osing tribe, this Jaranan Buto fashion will be developed into a casual fashion that is comfortable for daily use. The purpose of this research is to describe the creation process and the finished result of the creation of a casual fashion design with the source idea of Jaranan Buto. This research method uses the creation method, which has 3 stages, namely exploration, design, and realization. The results of this research are (1) the process of creating a casual fashion design with the idea source of Jaranan Buto, (2) the results of creating 3 casual outfits with the idea source of Jaranan Buto, consisting of 2 casual female outfits and 1 casual male outfit. 2 casual outfits consisted of 2 parts, namely tops and pants, while 1 casual outfit consisted of 3 parts, namely tops, pants, and obi.